2018
DOI: 10.1093/mnras/sty3157
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamical analysis of the triply eclipsing hierarchical triple system EPIC 249432662

Abstract: Using Campaign 15 data from the K2 mission, we have discovered a triply-eclipsing triple star system: EPIC 249432662. The inner eclipsing binary system has a period of 8.23 days, with shallow ∼3% eclipses. During the entire 80-day campaign, there is also a single eclipse event of a third-body in the system that reaches a depth of nearly 50% and has a total duration of 1.7 days, longer than for any previously known thirdbody eclipse involving unevolved stars. The binary eclipses exhibit clear eclipse timing var… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 81 publications
0
53
0
Order By: Relevance
“…This led us to collect all the observations and then carry out a complex photodynamical light curve and ETV analysis (see e.g. Borkovits et al 2019a). For this purpose, we used the simple aperture photometry (SAP) data.…”
Section: Tic 167692429mentioning
confidence: 99%
See 2 more Smart Citations
“…This led us to collect all the observations and then carry out a complex photodynamical light curve and ETV analysis (see e.g. Borkovits et al 2019a). For this purpose, we used the simple aperture photometry (SAP) data.…”
Section: Tic 167692429mentioning
confidence: 99%
“…(4) Finally, four (five) other parameters that are related (almost) exclusively to the light-curve solutions, as follows: the duration of the primary eclipse ( t) pri closest to epoch t 0 (which 5 Two other inner-orbit related parameters, namely the instantaneous orbital periods (P 1 ) and inferior conjunction time (T 0 ) 1 of the secondary components of the inner binaries, i.e. the mid-primary-eclipse-times, were constrained with the use of the ETV curves in the manner explained in appendix A of Borkovits et al (2019a), whilst the sixth orbital element, 1 , as irrelevant, was kept fixed at zero. 6 As 1 = 0 • was assumed at epoch t 0 for all runs, 2 set the initial trial value of the differences of the nodes (i.e.…”
Section: J O I N T P H Y S I C a L A N D Dy Na M I C A L M O D E L L mentioning
confidence: 99%
See 1 more Smart Citation
“…The two periods (P A,B ) and reference primary eclipse times ((T 0 ) A,B ) of both binaries were not adjusted, but constrained through the ETV curves, as was explained in the Appendix A of Borkovits et al (2019b). Furthermore, the systemic radial velocity of the center of mass of the whole quadruple system (γ) which in the current model occurs only as an additive parameter independent of any other parameters, was calculated in each trial step by simply minimizing a posteriori the goodness of fit of the RV curve (i.e.…”
Section: Combined Light Rv and Etv Curve Analysis Withmentioning
confidence: 99%
“…Other multiply-eclipsing systems include KIC 4247791 (Lehmann et al [207]) which shows two sets of eclipses plus spectral lines from four stars; KIC 6543674, which shows eclipses on a 2.39 d period with extra eclipses from a third body on a 1090-d orbit (Masuda et al [208]); KIC 7177553 which shows four sets of spectral lines and one set of eclipses (Lehmann et al [209]); and the doubly-eclipsing systems EPIC 219217635 and EPIC 249432662 (Borkovits et al [210,211]) observed during the K2 mission and showing eclipse timing variations due to being hierarchical multiple systems. KIC 2856960 shows eclipses on a 0.258 d period and forests of eclipses every 204 d (Figure 6; Armstrong et al [212]), similar to KIC 4150611, but its configuration remains unclear as no model has been found that satisfies the observations (Marsh et al [213]).…”
Section: Multiple Eclipsersmentioning
confidence: 99%